Cutting Tools
Patent Information
- Application Number
- JP2023579043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-23
- Filing Date
- 2022-06-17
- Publication Date
- 2025-04-28
AI Technical Summary
Existing methods for joining steel and cemented carbide in cutting tools face challenges such as non-uniform hardness profiles, residual stresses, and negative impacts on superhard materials like PCD or cBN due to localized heating, leading to issues like wear and cracking.
A cutting tool design featuring a brazed joint between maraging steel and cemented carbide with a TiC layer, using active brazing to ensure a uniform hardness profile and strong, predictable joints, while minimizing adverse effects on superhard materials.
The method achieves a strong, uniform hardness profile in the steel section, enhancing wear resistance and joint strength, and prevents damage to PCD or cBN materials, facilitating a more reliable and durable cutting tool.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cutting tool comprising a cemented carbide section comprising a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate and a maraging steel section, the sections being joined by brazing. The present invention also relates to the manufacture of such a cutting tool. [Background technology]
[0002] The use of polycrystalline diamond (PCD) or cubic boron nitride (cBN) in cutting tools is known in the art. In many cases, the PCD or cBN material is bonded to a cemented carbide substrate. There are several reasons for this, including simplifying manufacturing and also because the Co in the cemented carbide infiltrates the PCD or cBN material during manufacturing and therefore acts as a catalyst or binder for the PCD or cBN material.
[0003] Joining steel to cemented carbide by brazing or welding has long been known in the field of tool manufacturing. Joining steel to cemented carbide presents several challenges, for example, differences in CTE (coefficient of thermal expansion), strength of brazed joints, and undesirable hardness profile of steel.
[0004] There are several solutions that can improve each of these problems individually, but these solutions often introduce problems in other areas and do not solve all of the problems.
[0005] The principle of brazing is the use of a brazing material that when heated joins two parts. There are several ways to heat the brazed joint, one of the most common is induction heating using an induction coil. One advantage of using a coil is that only a localized area around the brazed joint is heated, leaving the rest of the tool unaffected. However, this localized heating can result in an unwanted hardness profile in the steel part, which can cause problems when the steel part is provided with threads for fixing rotary tools and other cutting tools, etc. It can also result in residual stresses caused by uncontrolled cooling, uneven heat distribution (skin effect) and unwanted lattice transformations.
[0006] Another disadvantage of using coils for heating is that each tool must be handled individually; a more automated industrial process would be preferable.
[0007] Heating the entire steel and cemented carbide section makes the hardness profile more uniform, but then the increased temperature affects the entire steel section, thus reducing the overall hardness.
[0008] Another problem that can occur when threads are provided in steel parts for fastening cutting tools is wear: since the same tool, e.g. a shank, is preferably used for a long period of time, leading to frequent replacement of cutting tools, wear of the threads can have a negative effect on the fastening of the cutting tool, e.g. the tool can become stuck and cannot be removed.
[0009] Another problem is that high brazing temperatures can have a negative effect on PCD or cBN materials. High temperatures can cause stresses that can lead to cracks. For PCD, high temperatures can also cause graphitization of the diamond particles.
[0010] One object of the present invention is to provide a cutting tool having both strong brazed joints and steel sections with a uniform hardness profile and high hardness resulting in improved wear resistance.
[0011] Another object of the present invention is to provide an easy to use method for joining steel and cemented carbide, resulting in a predictable joint that is high strength and a steel part that has a predictable hardness.
[0012] Another object of the present invention is to provide a method for joining steel parts and ultra-hard parts comprising a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate, which method does not have a negative effect on the PCD or cBN material. [Brief description of the drawings]
[0013] [Figure 1] Figure 1 shows a schematic diagram of the tool: A is the steel part, B is the brazed joint, C is the cemented carbide support and D is the superhard compact. [Diagram 2] FIG. 2 shows an SEM image at a magnification of 10,000 of the contact surface between the cemented carbide part of Invention 1 and the brazing material in Example 1. [Diagram 3] FIG. 2 shows an SEM image at a magnification of 40,000 of the contact surface between the cemented carbide part of Invention 1 and the brazing material in Example 1. [Figure 4] FIG. 1 shows EDS mapping of element Ti at the contact surface between the cemented carbide part of Invention 1 and the brazing material in Example 1 at a magnification of 10,000. [Diagram 5] FIG. 1 shows the hardness profile of a tool using induction heating: A: steel part, B: brazed joint, C: cemented carbide. [Figure 6] FIG. 1 shows a schematic diagram of the shear test apparatus, 1 is the steel part and 2 is the cemented carbide part. [Figure 7] 1 shows different parts of the brazed joint of invention 1. A is the cemented carbide part and B is the maraging steel part. [Figure 8] 1 shows different parts of the brazed joint of invention 1. A is the cemented carbide part and B is the maraging steel part. [Figure 9] 1 shows different parts of the brazed joint of invention 1. A is the cemented carbide part and B is the maraging steel part. [Figure 10] FIG. 1 shows the steps of the claimed method, where A is providing a cemented carbide section, B is providing a maraging steel section, C is disposing a braze material between the cemented carbide section and the maraging steel section, D is brazing, and E is aging. [Figure 11] FIG. 1 shows examples of brazed tools: A is a PCD part supported on a cemented carbide, B is a maraging steel part. [Figure 12] FIG. 1 shows a hardness measurement pattern in a cross section of a steel part of Invention 2 in Example 1. [Figure 13] FIG. 1 shows the results of hardness measurements performed on Invention 2 in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention relates to - Ultra-hard sections comprising sintered bodies of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate; - Maraging steel sections with hardness of 350-580HV1 with a standard deviation of 0-20HV1 The cutting tool further comprises a brazed joint joining the cemented carbide substrate and the maraging steel portion, the brazed joint comprising Ti, and the brazed joint comprising a TiC layer having a thickness of 0.03 to 5 μm adjacent to the cemented carbide.
[0015] By PCD (polycrystalline diamond) sintered bodies is meant herein a material containing diamond crystals sintered together, the amount of diamond crystals being 50-100 vol%. The diamond crystals typically have a grain size of 0.5-30 μm. The PCD sintered bodies may also contain one or more elements selected from Al, Cr, Co, Ni, V, Fe and Si.
[0016] By cBN sintered body is meant herein a material comprising cBN grains embedded in a metal and / or ceramic binder, the amount of cBN grains being between 30 and 99 vol %. The ceramic binder may contain one or more components which are carbides, nitrides, carbonitrides, borides or oxides of Co, Ni and elements selected from Groups 4 to 6 of the Periodic Table of the Elements.
[0017] Polycrystalline diamond (PCD) and cubic boron nitride (cBN) sintered bodies are typically manufactured by providing a suitable powder mixture and subjecting it to a high-pressure, high-temperature (HPHT) sintering process to form a sintered body. When bonding a compact to a cemented carbide substrate, one way to do this is to use a cup with a cemented carbide disk at the bottom. The cup is then filled with a powder mixture of the selected PCD or cBN and then the cup is sealed. The sealed cup is then subjected to a high-pressure, high-temperature (HPHT) sintering process. The PCD or cBN material is bonded to the cemented carbide during the sintering process. The disk can then be cut into suitable pieces, for example using a laser or WEDM (wire electrical discharge machining).
[0018] The cemented carbide used as the substrate for the sintered PCD or cBN body can be made from any cemented carbide common in the art. Cemented carbide comprises a hard phase embedded in a metallic binder phase matrix.
[0019] By hardmetal in this specification it is meant that at least 50 wt% of the hard phase is WC.
[0020] Suitably, the amount of the binder metal phase is 3-20 wt%, preferably 4-15 wt% of the cemented carbide. Preferably, the main component of the binder metal phase is selected from one or more of Co, Ni and Fe, more preferably, the main component of the binder metal phase is Co.
[0021] By major component in this specification it is meant that no other elements are added to form a binder phase, but if another component, e.g. Cr, is added, it will necessarily dissolve in the binder during sintering.
[0022] In one embodiment of the present invention, the cemented carbide may also contain other components common in cemented carbide elements selected from Cr, Ta, Ti, Nb and V present as elements or as carbides, nitrides or carbonitrides.
[0023] Maraging steels are a type of steel that is hardened by the precipitation of intermetallic compounds. Maraging steels suitably contain 13-25 wt% Ni, and one or more alloying elements selected from Co, Mo, Ti, Al and Cr in a total amount of 10-27 wt%, preferably 11-23 wt% of the alloying elements. Maraging steels typically contain less carbon than conventional steels, suitably 0.03 wt% or less. The balance is Fe.
[0024] The maraging steel according to the invention preferably contains 11-25 wt% Ni, preferably 17-25 wt% Ni. The alloying elements are suitably Co in an amount of 7-15 wt%, preferably 8.5-12.5 wt% Co, Mo in an amount of 3-10 wt%, preferably 3-6 wt% Mo, Ti in an amount of 0.1-1.6 wt%, preferably 0.5-1.2 wt% Ti, 0-0.15 wt% Cr, 0-0.2 wt% Al, less than 0.1 wt% Mn, any of P and S, and less than 0.03 wt% C. The balance is Fe.
[0025] In one embodiment of the present invention, the maraging steel has a composition of 17 to 19 wt% Ni, 8.5 to 12.5 wt% Co, 4 to 6 wt% Mo, 0.5 to 1.2 wt% Ti, 0 to 0.15 wt% Cr, 0 to 0.2 wt% Al, less than 0.1 wt% Mn, any one of P and S, and less than 0.03 wt% C. The balance is Fe.
[0026] The average hardness of the maraging steel portion is suitably 350 to 580 HV1, preferably 400 to 580 HV1, and more preferably 410 to 580 HV1.
[0027] Hardness is measured by a Vickers hardness tester, applying a load of 1 kgf (kilogram force) and a load time of 15 seconds. A pattern of at least 15 dimples, uniformly distributed across the cross section (not the surface) of the maraging steel part, should be applied. Uniformly distributed across the cross section in this specification means that the dimples should be placed to cover the entire cross section, even if the distance between the dimples varies slightly.
[0028] The average value is the average of the hardness values at these measurement points. The standard deviation of the hardness values is suitably 0 to 20 HV1, and preferably 0 to 14 HV1.
[0029] The brazing technique is so-called active brazing. It means that the joint is not only formed by melting the brazing material to form a metallic bond, but also involves a chemical reaction with one or both of the materials to be joined. The reactive element in the brazing material is usually Ti, but elements such as Hf, V, Zr and Cr are also considered to be active elements. According to the present invention, Ti is the active element.
[0030] By braze joint herein is meant the area or mass between the cemented carbide and the maraging steel section that is filled by the braze material and formed during the brazing process, see below.
[0031] The thickness of the brazed joint is suitably 5 to 200 μm, preferably 15 to 100 μm.
[0032] The brazed joint is not a homogeneous phase, rather, after brazing, the elements in the braze material form different phases.
[0033] The brazed joint contains Ti, which during brazing reacts with the carbon in the tungsten carbide of the cemented carbide part to form a TiC layer at the interface between the brazed joint and the cemented carbide part.
[0034] There are several ways to detect the presence of a TiC layer, depending on the type of equipment used.
[0035] When using a scanning electron microscope (SEM) with sufficiently high resolution, the TiC layer is clearly visible adjacent to the hardmetal section, see for example Figures 2 and 3. To confirm the composition of the layer, SEM-EPMA (Electron Probe Microscopy Analysis) with SEM-EDS (Energy Dispersive Spectroscopy) and / or WDS (Wavelength Dispersive Spectroscopy) can be used to confirm the individual elements of the TiC layer.
[0036] If the SEM used does not have sufficient resolution to show the TiC layer, the accumulation of Ti and / or C at the interface between the brazing material and the cemented carbide substrate can be seen, for example, using SEM-EPMA with SEM-EDS or WDS. The accumulation of Ti is hereafter referred to as the Ti accumulation layer (see, for example, FIG. 4) and is one indicator that a TiC layer is formed, even if it is not visually detected in the SEM image. The Ti accumulation layer is considerably thicker than the actual TiC layer, which may mean that not all Ti forms TiC. The thickness of the Ti accumulation layer is also partially influenced by the analysis method.
[0037] In one embodiment of the present invention, the thickness of the TiC layer is 0.03 to 5 μm, more preferably 0.05 to 0.5 μm, and most preferably 0.05 to 0.25 μm.
[0038] Preferably, the brazed joint further comprises one or more elements selected from Ag, Cu, Sn, In, Zr, Hf, Cr, more preferably from Ag, Cu and In.
[0039] The composition of the brazed joint after brazing is difficult to determine because the elements are not uniformly distributed. If possible, the easiest way is to look at the brazing material used, since the paste or foil is a uniform blend. Additionally, the brazed joint may contain small amounts of elements from the materials being joined, e.g. Co, W, etc. from cemented carbide, and Fe, Ni, etc. from maraging steels.
[0040] The amount of Ti and other elements in the brazed joint can also be measured using energy dispersive X-ray spectroscopy (EDS). However, due to the non-uniform distribution of the elements in the brazed joint, many measurement points need to be used and the standard deviation is large. Preferably, the brazed joint contains, on average, Ag in an amount of 30-80 wt%, preferably 40-75 wt%, Cu in an amount of 15-65 wt%, preferably 20-40 wt%, Ti in an amount of 0.3-15 wt%, preferably 0.5-5 wt%, Sn in an amount of 0-10 wt%, preferably 0-2 wt%, and In in an amount of 0-30 wt%, preferably 10-25 wt%, the remainder being unavoidable impurities.
[0041] By inevitable impurities we mean small amounts of elements other than those listed above that may be present in the brazing material before the brazing process, as well as elements from the materials being joined, e.g. Co, W, etc. from cemented carbide, and Fe, Ni, etc. from maraging steel. When subjected to high temperatures during the brazing process, the brazing material melts and allows diffusion from the joint site, small amounts of elements from the joint site are inevitably dissolved in the brazing material. As long as the brazing process parameters, such as temperature and time, are within the ranges according to the invention, the total amount of inevitable impurities is small and does not affect the performance of the brazed joint.
[0042] The brazed joint suitably has a shear strength of at least 130 MPa, preferably at least 140 MPa, more preferably 140-300 MPa. The shear strength is measured by a shear test.
[0043] At the contact surface between the brazed joint and the maraging steel part, Ti is also accumulated at the brazed joint, and Ti forms a metallic bond with the iron in the steel. The thickness of the accumulated layer of Ti on the maraging steel surface is preferably 1 to 10 μm, preferably 2 to 5 μm, and can be measured, for example, by EDS.
[0044] In one embodiment of the invention, the maraging steel is 1.2709, the cemented carbide has a composition of 4-15 wt% Co, 0.1-1 wt% Cr and the balance WC, and the brazed joint has an average composition of 58-62 wt% Ag, 22-26 wt% Cu, 13-15 wt% In and 1.5-2.5 wt% Ti.
[0045] The cutting tool may be a tool or part of a tool in which a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate is joined to a steel part by brazing, such as the cutter shown in FIG. 11.
[0046] The present invention relates to a method for producing a cutting tool according to the above, comprising the following steps: - providing a cemented carbide part comprising a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate; and maraging steel sites; - disposing a brazing material comprising Ti in an amount of 0.3-15 wt. % of the brazing material between and in contact with the cemented carbide substrate and the maraging steel section; - subjecting the cemented carbide supported cemented carbide section and the maraging steel section with the brazing material therebetween to a brazing process in a furnace at a temperature of 600-780°C, preferably 650-750°C, more preferably 700-740°C, for a period of 1-60 minutes, wherein the brazing is carried out in vacuum; - subjecting at least the maraging steel portion to an aging process at a temperature of 300-600°C for 5 minutes to 12 hours; The present invention also relates to a method, comprising:
[0047] The ultra-hard part, including a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN), and the maraging steel part have the composition described above. The hardness of the maraging steel prior to brazing may vary from that described above depending on the grade of the maraging steel and whether the steel has been aged or not. In one embodiment, the maraging steel is provided solution annealed with a hardness of about 340 HV1.
[0048] The shape and size of the superhard section and the maraging steel section will depend on the type of tool being produced.
[0049] The brazing material according to the present invention (also called filler metal or solder) contains a total amount of Ti of 0.3-15 wt % of the brazing material, preferably 1-5 wt %. The brazing material according to the present invention suitably has a solidus temperature of 488-1123°C, preferably 600-700°C. Furthermore, the brazing material according to the present invention has a liquidus temperature of 612-1180°C, preferably 700-750°C. In addition to Ti, the brazing material further contains one or more elements selected from Ag, Cu, Sn, In, Zr, Hf and Cr.
[0050] In one embodiment of the present invention, the brazing material comprises Ag in an amount of 30-80 wt%, preferably 40-75 wt%, Cu in an amount of 15-65 wt%, preferably 20-40 wt%, Ti in an amount of 0.3-15 wt%, preferably 0.5-5 wt%, Sn in an amount of 0-10 wt%, preferably 0-2 wt%, and In in an amount of 0-30 wt%, preferably 10-25 wt%.
[0051] Preferably the brazing material is provided as a foil or a paste.
[0052] A braze material is provided on the faying surfaces of the cemented carbide substrate and the steel part.
[0053] The thickness of the brazing material before the brazing process depends on the type of material, i.e. foil or paste. If a paste is used, enough material is applied so that the surfaces to be brazed are covered. Typically the thickness is 20-200 μm, preferably 50-100 μm.
[0054] The parts are then placed in a furnace with an inert or reducing environment, i.e., a minimum amount of oxygen. Preferably, the brazing temperature in the furnace is 600-780°C, preferably 650-750°C, more preferably 730-740°C. The time the parts are subjected to high temperature is 1-60 minutes, preferably 5-15 minutes. If the time at high temperature is shorter, there is not enough time to form the brazed joint and for the Ti to react and reach the desired strength of the brazed joint. If the time at high temperature is longer, brittle reaction zones containing Ti will grow in an uncontrolled manner, negatively affecting the joint properties, e.g., shear strength.
[0055] Brazing is preferably carried out in a vacuum or in the presence of a low partial pressure of argon. Vacuum, as used herein, refers to a pressure in the furnace of less than 5×10 -4 Less than mbar, preferably 5×10 -5 mbar. If argon is present, the argon pressure is less than 1×10 -2 Less than mbar.
[0056] During the brazing in the furnace, a clamping force may be applied to further strengthen the braze. Clamping force here means the application of force by pressing the steel and the cemented carbide sections against each other, preferably by placing an external weight on the carbide section. The force acting on the brazed joint by the weight of the cemented carbide section or the maraging steel section, depending on which section is on top of the other section, is not included in these values.
[0057] In one embodiment, a clamping force of 0.5 to 10 MPa, preferably 2 to 8 MPa, is applied.
[0058] In one embodiment of the present invention, no clamping force is applied.
[0059] After brazing, the part is subjected to an ageing step by subjecting the part to an elevated ageing temperature of 300-600°C, preferably 350-500°C, most preferably 400-440°C for 5 minutes to 12 hours, preferably 3-6 hours.
[0060] Preferably, the heating rate to the ageing temperature is 1-50° C. / min, preferably 5-10° C. / min. Preferably, the cooling rate from the ageing temperature to a temperature at least below the solidus temperature of the brazing material, preferably below 300° C., is 1-50° C. / min, preferably 5-10° C. / min.
[0061] The brazing furnace used according to the present invention can be any furnace capable of providing well-controlled conditions as described above with respect to vacuum, heating and cooling rates, etc. The brazing and aging steps can be carried out either in the same furnace or in two separate furnaces.
[0062] It is common for steel parts to be subjected to machining operations such as threading, grinding, etc. In order to be able to machine the steel part, the hardness cannot be too high and depending on the type of maraging steel grade selected, an ageing step can be performed before or after machining of the steel part to achieve the desired hardness and wear resistance in the final tool.
[0063] In one embodiment of the present invention, the ageing is carried out directly after the brazing step and any machining of the steel, such as for example thread cutting, is carried out on the already aged maraging steel, i.e. after the ageing step.
[0064] In another embodiment of the invention, the ageing is carried out after any machining of the steel, such as for example thread cutting. EXAMPLES
[0065] Example 1 (Invention)
[0066] Steel sections made from maraging steel 1.2709 were provided along with cemented carbide sections having a composition of 10 wt% Co, 1 wt% other carbides and the remainder WC.
[0067] The brazing material was provided in the form of a paste (TB-629) manufactured by Tokyo Blaze Co., Ltd., and was applied in a thin layer but in an amount sufficient to cover the surfaces to be brazed. The brazing material had a composition of 58-62 wt% Ag, 22-26 wt% Cu, 1.5-2.5 wt% Ti, and 13-15 wt% In. The solidus temperature is about 620°C and the liquidus temperature is about 720°C.
[0068] The paste was placed between the maraging steel part and the cemented carbide part so that both parts were in contact with the paste. The assembled joint parts were then placed in a Torvac vacuum furnace where the temperature was first raised to 350°C at a rate of 20°C / min. After a 10 minute hold for debinding the brazing material at 350°C, the parts were heated to 600°C at a rate of 20°C / min. After a 10 minute hold at 600°C, the parts were heated to 740°C at a rate of 5°C / min. After a 20 minute hold at the brazing temperature of 740°C, the parts were cooled to 300°C at a rate of 5°C / min. After 300°C, free cooling was allowed.
[0069] After the brazing process, the brazed parts were subjected to an ageing process to increase the hardness of the maraging steel. Three different ageing temperatures were tested and one brazed part was not subjected to the ageing process for comparison. The parts were placed in a furnace and the temperature was raised to the ageing temperature at a rate of 5°C / min. The different ageing temperatures applied were 355, 440 and 490°C. The ageing temperature was held for 3 hours after which the parts were cooled to 300°C at a rate of 5°C / min. After 300°C, they were allowed to cool freely. TIFF2024527282000002.tif46170
[0070] Example 2 (Comparison) Steel parts made of steel 1.6582 (34CrNiMo6) were provided along with cemented carbide parts with a composition of 10 wt% Co and 0.4 wt% Cr with the balance WC.
[0071] The brazing material was Ag49Zn23Cu16Mn7.5Ni4.5 in wire form applied as a ring with a diameter of 1-2 mm.
[0072] The parts were joined by induction heating using a coil to rapidly heat the braze joint to 700°C and hold for 15 seconds, after which the powder was cut off and the tool was allowed to cool to room temperature. The hardness values of the steel part are shown in Figure 5, where the measurement points are placed along a line from the braze joint of the steel part, across the braze joint to the cemented carbide part.
[0073] This sample is designated herein as Comparative 2.
[0074] Example 3 (Comparison) Steel sections made of carbon hardened hot work steel 1.2344 were provided along with cemented carbide sections with a composition of 10 wt% Co, 1 wt% other carbides and the remainder WC. The hot work steel parts were in the pre-hardened condition. The steel was quenched from 1060°C with N2 in a vacuum furnace and then relaxed three times at 200°C for 10 minutes. The average hardness value of the quenched 1.2344 sections was 582 HV1 with a standard deviation of 66 HV1.
[0075] Brazing material 1 was provided in the form of a paste. Brazing material 2 was provided in the form of a foil having a thickness of 100 μm. Brazing material 1 had a composition of 60.0 wt% Ag, 24.0 wt% Cu, 14.0 wt% In, and 2.0 wt% Ti. The solidus temperature was about 620° C. and the liquidus temperature was about 720° C. Brazing material 2 had a composition of 59.0 wt% Ag, 27.25 wt% Cu, 12.5 wt% In, and 1.25 wt% Ti. The solidus temperature was about 605° C. and the liquidus temperature was about 715° C.
[0076] The brazing material was placed between the maraging steel part and the cemented carbide part so that both parts were in contact with the brazing material. The assembled joint parts were placed in a furnace where the temperature was first raised to 500 °C at a rate of 20 °C / min and held for 5 minutes. The temperature was then raised from 500 °C at a rate of 50 °C / min to different brazing temperatures T between 685 °C (brazing material 1) and 715 °C (brazing material 2). ろう付け I raised it up to T ろう付け was held for a dwell time of 4 minutes, after which the parts were allowed to cool to room temperature by free cooling.
[0077] The hardness was measured and the results are shown in Table 2.
[0078] The two samples, 685°C (Braze Material 1) and 715°C (Braze Material 2), are designated herein as Comparatives 3 and 4, respectively.
[0079] Shear strength values were not determined.
[0080] Example 4 (Comparison) Steel parts made from carbon-hardening hot-work steel 1.2344 were provided along with cemented carbide parts having a composition of 10 wt% Co, 1 wt% other carbides and the remainder WC.
[0081] The brazing material was provided in the form of a foil having a thickness of 100 μm. The brazing metal had a composition of 100.0 wt% Cu. The melting temperature was 1085° C.
[0082] The foil was placed between the steel and maraging cemented carbide parts and the assembled joint parts were placed in a furnace, where the temperature was first increased to 650 °C at a rate of 20 °C / min and held for 5 min. The temperature was then increased from 650 °C at a rate of 10 K / min to the brazing temperature T of 1100 °C. ろう付け I raised it up to T ろう付け The temperature was kept for a dwell time of 15 min, after which the parts were cooled at a cooling rate of 50 K / min to 850 °C. From 850 °C, 2 bar overpressure and 2500 min were applied. -1The specimens were quenched with N2 at a fan frequency of .
[0083] The cemented carbide-steel joints were then aged twice with carbon hardened hot work steel 1.2344 at 630°C for 2 hours.
[0084] This sample is designated herein as Comparative 5.
[0085] Example 5 (Comparison) Steel parts made from carbon hardened cold work steel 1.2714 were provided along with cemented carbide parts having a composition of 10 wt% Co, 1 wt% other carbides and the balance WC.
[0086] The brazing metals were provided in the form of foils having a thickness of 100 μm. Brazing material 1 had a composition of 100.0 wt% Cu. The melting temperature was 1085° C.
[0087] The foil was placed between the maraging steel and the cemented carbide parts, and the assembled joint parts were placed in a furnace, where the temperature was first increased to 650 °C at a rate of 20 °C / min and held for 5 min. The temperature was then increased from 650 °C at a rate of 10 K / min to the brazing temperature T of 1100 °C. ろう付け I raised it up to T ろう付け The mixture was held for a dwell time of 15 minutes. After the dwell time, free cooling to room temperature was started.
[0088] The cemented carbide-steel joints, along with the carbon hardened cold work steel 1.2714 sections, were then heated by torch to a temperature of 850°C for 10 minutes, then quenched in oil to room temperature, followed by tension relaxing in a vacuum furnace at 200°C for 2 hours.
[0089] The cemented carbide-steel joints were then aged at 500°C for 2 hours along with carbon hardened cold work steel 1.2714 sections.
[0090] This sample is designated herein as Comparative 6.
[0091] Example 6 The assembled joint parts were evaluated by measuring the shear strength of the brazed joints, the hardness of the maraging steel sections and, where applicable, the TiC layer and the TiC build-up layer of the brazed joints.
[0092] To evaluate the strength properties of the joints, shear tests of the specimens were carried out using a shearing device set up as shown in Figure 6, where 1 is the steel part in the shape of a steel cylinder (φ=20 mm, h=5 mm) and 2 is the cemented carbide part in the shape of a cemented carbide cylinder (φ=10 mm, h=5 mm). The steel cylinder is placed in the gap of the shear strength test device and can therefore only be moved in the loading direction. Notches eroded on the surface of the device hold the joined parts in the correct position and ensure the induction of a uniformly distributed force into the brazed joint. The applied force is constantly increased until the brazed joint breaks and the cemented carbide cylinder is chipped off. The maximum measured force measured and the initial joint surface (A=78.5 mm) are then compared. 2 The ultimate shear strength was calculated by the quotient of (1) and (2). The braze material was not removed prior to determining the shear strength of the brazed joint.
[0093] The hardness of the maraging steel 1.2709 section was measured using a Vickers hardness tester by applying a load of 1 kgf (kilogram force) and a load time of 15 seconds to the cross section of the maraging steel section. 2 A pattern of 3×6 recesses was applied covering the 100 mm square of ...
[0094] For inventions 1-3, SEM-EDS technique was used to analyze the contact surface between the brazed joint and the cemented carbide. The SEM used was a Jeol JSM-7001F, a high-resolution field emission scanning electron microscope (FE-SEM) equipped with a thermal field emission cathode (Schottky). The thickness of the TiC layer at the brazed joints of inventions 1-3 was measured on SEM images at a magnification of 10,000. The TiC layer was confirmed by visual appearance in backscattered electron mode. Figure 3 shows an SEM image of invention 3, where the TiC layer is clearly visible. All values of the TiC layer thickness given in Table 2 are the average of three measurements taken in the center of the brazed joint, i.e. away from the edges.
[0095] Using EDS, the accumulation of Ti could be confirmed and measured as a Ti accumulation layer. Accumulation layer herein refers to the thickness of the accumulation estimated from the EDS scan. The values in Table 2 are estimates from visual inspection of the EDS scans and are therefore given as intervals.
[0096] All TiC layer thicknesses in Table 2 are the average of three measurements taken in the center of the brazed joint, i.e. away from the edge of the SEM image at 10,000 magnification.
[0097] In FIG. 4, the accumulation of Ti is shown using EDS. TIFF2024527282000003.tif90170
Claims
1. a cemented carbide portion comprising a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate; a maraging steel section having a hardness of 350-580 HV1 with a standard deviation of 0-20 HV1; a brazing joint that joins the cemented carbide substrate and the maraging steel portion; A cutting tool comprising: the braze joint comprises Ti, and the braze joint comprises a TiC layer adjacent to a cemented carbide substrate having a thickness of 0.03 to 5 μm; cutting tools.
2. 2. The cutting tool of claim 1, wherein the maraging steel section has a hardness of 400-580 HV1 with a standard deviation of 0-14 HV1.
3. The cutting tool of claim 1 , wherein the braze joint has a thickness of 5 to 200 μm.
4. 10. The cutting tool of claim 1, wherein the brazed joint has a shear strength of at least 130 MPa.
5. The cutting tool of claim 1 , wherein the braze joint comprises Cu, Ag and In.
6. 2. The cutting tool of claim 1, wherein the brazed joint comprises Ag in an amount of 30-80 wt%, Cu in an amount of 15-65 wt%, Ti in an amount of 0.3-15 wt% and In in an amount of 10-25 wt% plus unavoidable impurities.
7. 2. The cutting tool of claim 1, wherein the maraging steel comprises 13-25 wt.% Ni, and one or more alloying elements selected from Co, Mo, Ti, Al and Cr in an amount of 10-27 wt.%, less than 0.3 wt.% C and balance Fe.
8. 2. The cutting tool of claim 1, wherein the maraging steel comprises 17-19 wt% Ni, 8.5-12.5 wt% Co, 4-6 wt% Mo, 0.5-1.2 wt% Ti, 0-0.15 wt% Cr, 0-0.2 wt% Al, less than 0.1 wt% of any of Mn, P, and S, and less than 0.03 wt% C, and the balance Fe.
9. 2. A method for manufacturing the cutting tool of claim 1, comprising the steps of: - providing a cemented carbide part comprising a sintered body of polycrystalline diamond (PCD) or cubic boron nitride (cBN) bonded to a cemented carbide substrate; - providing a maraging steel part; - disposing a brazing material comprising Ti in an amount of 0.3-15 wt % of the brazing material between and in contact with the cemented carbide substrate and the maraging steel section; - subjecting the ultra-hard section and the maraging steel section with the brazing material therebetween to a brazing process in a furnace at a temperature between 600 and 780°C for a period of between 1 and 60 minutes, the brazing being carried out in a vacuum; - subjecting at least the maraging steel part to an ageing step at a temperature between 300 and 600°C for 5 minutes to 12 hours; A method comprising:
10. The method of manufacturing a cutting tool according to claim 9, wherein the brazing step is carried out at a temperature of 600-780°C for a period of 5-15 minutes.
11. The method for manufacturing a cutting tool according to claim 9, wherein the ageing step is carried out at a temperature of 300-600° C. for 5 minutes to 12 hours.
12. 10. The method of manufacturing a cutting tool according to claim 9, wherein the braze material has a solidus temperature of 488-1123°C and a liquidus temperature of 612-1180°C, and the braze material further comprises, in addition to Ti, one or more elements selected from Ag, Cu, Sn, In, Zr, Hf and Cr.
13. The method for manufacturing a cutting tool according to claim 9, wherein a clamping force of 0.5 to 10 MPa is applied during the brazing process.